2014
DOI: 10.3174/ajnr.a4065
|View full text |Cite
|
Sign up to set email alerts
|

Mapping p53 Mutations in Low-Grade Glioma: A Voxel-Based Neuroimaging Analysis

Abstract: BACKGROUND AND PURPOSE:Brain tumor location has proved to be a prognostic factor that may be associated with features of neoplastic origin. Mutation of p53 is an atypical genetic change that occurs during tumorigenesis. Thus, a potential correlation may exist between tumor location and p53 status. The purpose of the current study was to identify anatomic characteristics of mutant p53 expression by using quantitative neuroimaging analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Tumor location is an influential factor associated with LGG-related epilepsy. Several MRI-based studies indicate the association between the involvement of eloquent (42), cortical (45), and insular regions (43) with epilepsy occurrence, along with the probabilistic risk atlas of LGG-related epilepsy (44). However, there is a need to investigate and predict the type of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor location is an influential factor associated with LGG-related epilepsy. Several MRI-based studies indicate the association between the involvement of eloquent (42), cortical (45), and insular regions (43) with epilepsy occurrence, along with the probabilistic risk atlas of LGG-related epilepsy (44). However, there is a need to investigate and predict the type of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a growing number of molecular mechanisms contributing to TMZ resistance in GBM including genetic and epigenetic, such as MGMT methylation (22), IDH mutations (23), aberrant ABC transporter expression (24,25), p53 mutations and deletions (26), DNA repair deregulation (27,28) and miRNAs (29,30). Furthermore, evidence is now beginning to demonstrate lncRNAs as having important roles in cancer therapy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, IDH1 mutation was commonly seen in left frontal lobe, where TERT mutation only exists as well[ 2 , 5 , 23 ]. Such investigations were performed in the context of MGMT and TP53[ 24 , 25 ]. In our study, we used a panel composed of IDH1/1p19q/TERT which is worldwide recognized in the precise diagnosis of glioma to demonstrate the anatomic distribution of different molecular subsets.…”
Section: Discussionmentioning
confidence: 99%